2020
DOI: 10.26434/chemrxiv.12162360.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homology Modeling and Docking Studies of TMPRSS2 with Experimentally Known Inhibitors Camostat Mesylate, Nafamostat and Bromhexine Hydrochloride to Control SARS-Coronavirus-2

Abstract: The rapid outbreak of SARS-Coronavirus 2 (SARS-CoV-2) caused a serious global public health threat. The spike ‘S’ protein of SARS-CoV-2 and ACE2 of the host cell are being targeted to design and discover new drugs to control Covid-19 disease. Similarly, a transmembrane serine protease, TMPRSS2 of the host cell has been found to play a significant role in proteolytic cleavage of viral spike protein priming to the receptor ACE2 present in human cell. However, three dimensional structure and inhibition mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…Structural insights into the interactions of the three inhibitors described above with TMPRSS2 have been reported via computational study [ 134 ]. The molecular docking analysis revealed that camostat and nafamostat interact directly with residues His296, Asp435, and Ser441 in the catalytic domain of TMPRSS2.…”
Section: Potential Small Molecule Inhibitors Of Early Viral Eventsmentioning
confidence: 99%
“…Structural insights into the interactions of the three inhibitors described above with TMPRSS2 have been reported via computational study [ 134 ]. The molecular docking analysis revealed that camostat and nafamostat interact directly with residues His296, Asp435, and Ser441 in the catalytic domain of TMPRSS2.…”
Section: Potential Small Molecule Inhibitors Of Early Viral Eventsmentioning
confidence: 99%
“…To understand the binding affinity and the intermolecular interaction of the chosen three drug molecules camostat, nafamostat, and leupeptin [16,[18][19][20] (https://clinicaltrials.gov/ct2/show/ NCT04353284) with the active site amino acids of TMPRSS2, the molecular docking simulation was performed. In prior to the docking simulation, the abovesaid three drug molecules were prepared by the Ligprep module of Schrödinger software [28].…”
Section: Preparation Of Ligands and Receptor For Dockingmentioning
confidence: 99%
“…Camostat mesylate, nafamostat, and leupeptin (Fig. 1) are the drugs chosen as the inhibitors of TMPRSS2, in which the drugs camostat and nafamostat are under clinical trial for COVID-19 [13,16,[18][19][20] (https://clinicaltrials.gov/ct2/show/NCT04353284) treatment, whereas leupeptin [21] is tested for its suitability against SARS-CoV-2 viral infection and also studied for its antiviral properties against SARS-CoV viruses [22,23]. To better understand the molecular binding mechanisms of these molecules, which are not completely known at the molecular dynamics level, we have computed the binding affinity, intermolecular interactions, and the stability of molecules from the molecular docking and the molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure of human TMPRSS2 is not available yet, homology modeling and in silico docking studies have demonstrated the molecular mechanisms of camostat mesylate, nafamostat, and bromhexine hydrochloride in inhibiting TMPRSS2 (Sonawane et al, 2020 ). In this respect, active site-specific inhibitors of TMPRSS2 can be used as potential antiviral agents against SARS-CoV-2.…”
Section: Antiviral Strategies Against Sars-cov-2mentioning
confidence: 99%